Democracy and decision : the pure theory of electoral preference - Brennan, Geoffrey, 1944-; Lomasky, Loren E. (New York, NY, USA : Cambridge University Press, 1993)
Do voters in large-scale democracies reliably vote for the electoral outcomes they want? Is voting essentially like choosing a job or selecting an asset portfolio? Or is it more like cheering at a football match? And if the latter, what are the implications for the functioning of democracy when policies are determined by who cheers the loudest? This book is concerned with answering these questions. In the most narrow construction, the book offers a critique of the interest-based theory of voting behavior characteristic of modern "public choice" theory - and does so using the decision-theoretic apparatus of standard economics. The central claim is that fully rational voters will not reliably vote for the political outcomes they prefer. The broader objective of the book is to present an "expressive" theory of electoral politics as an alternative to the "interest-based" account. The authors argue that this expressive theory is both more coherent and more consistent with what is observed than is the interest-based orthodoxy. In particular, they believe that this theory can explain, for example, the propensity of democratic regimes to make war; the predominance of moral questions (the sexual conduct of candidates or the abortion issue) on the political agenda; and the distributive activities of democratic governments - facts that represent something of a challenge to the interest-based account. The significance of this account should be clear. If, as economists frequently assert, proper diagnosis of the disease is a crucial prerequisite to treatment, then the design of appropriate democratic institutions depends critically on a coherent analysis of the way the electoral process works and the perversities to which it is prone. The claim is that the interest-based account incorrectly diagnoses the disease. Accordingly, this book ends with an account of the institutional protections that go with expressive voting.
Machine derived contents note: 1. Ethics, politics and public choice -- 2. The logic of electoral choice -- 3. The nature of expressive returns -- 4. The analytics of decisiveness -- 5. The theory of electoral outcome: implications for public choice theory -- 6. From anecdote to analysis -- 7. Interpreting the numbers -- 8. Consensus, efficiency and contractarian justification -- 9. Paternalism, self-paternalism and the state -- 10. Towards a democratic morality -- 11. Constitutional implications -- Bibliography.
Includes index.
Includes bibliographical references (p. 226-231) and index.
Keywords: Voting; Social choice; Pressure groups; Democracy; Voter behaviour; Social choice; Nonparty political bodies; Democracy; Decision making; Mathematical models; Overseas item